Slow pyrolysis of chemically treated walnut shell for valuable products: Effect of process parameters and in-depth product analysis - Gupta S.; Gupta G.K.; Mondal M.K. (My University, 2025)
Pyrolysis is important method to harness bio-energy from not easily degradable biomass to meet today's energy requirement. The fixed bed slow pyrolysis of walnut shell was performed in continuous inert atmosphere to find out the effect of process parameters like temperatures (300–600 °C), particle size (0.25–1.00 mm), and bed height (8–12 cm) on yield and product characteristics. Walnut shell was pretreated with phosphoric acid at different concentrations (0.2–0.8 M) to improve yield and properties of pyrolysis products by removing inorganics and solubilizing lignin-hemicellulose components of biomass. Pretreatment showed enhanced biochar and bio-oil yield. Characterization of biochar was done using proximate, ultimate analyses, FTIR, XRD, SEM-EDX, etc. The physicochemical properties of liquid product such as viscosity, density, carbon residue, HHV and FTIR were determined. Pyrolytic gas composition was analyzed using GC-TCD and GC-FID. The properties of biochar inferred its utility as solid fuel or in waste water treatment as it has high BET surface area. The properties of bio-oil disclose its utility as blend fuel or a source of different valuable chemicals. Presence of CH4, H2 and CO in pyrolytic gas recommends good combustion behaviour. Thus above results describe the bio-energy potential of walnut shell. © 2019 Elsevier Ltd